Development and validation of educational technology for adolescents with Type 1 Diabetes Mellitus (Research, Society and Development, 2021)
Type 1 Diabetes Mellitus (Type 1 DM) is a chronic disease of multifactorial character, which can reach any age, being more common in children, adolescents and young people. DM can be administered through four basic pillars: insulin therapy, diet therapy, monitoring glycemic control and physical exercise. Health education is an important tool that can be used to contribute to some of these pillars. The objective was to develop an educational technology for adolescents with type 1 DM. This is a methodological study. The steps were: 1) Approval of the project by the Research Ethics Committee; 2) Literature and document review; 3) Content selection; 4) Construction of the story in a comic; 5) Internal validation. In the statistical analysis, the global Content Validity Index (CVI) of educational technology was 95% between content judges and technical judges. Among design and marketing specialists, educational technology was considered to be superior material, 94.61%. The evaluation of the content judges, classified the educational technology validated with an IVC of 0.96. The CVI of educational technology was 1.0, confirming the validation of its appearance and content with the group of technical and advertising and marketing judges. Thus, the educational booklet is valid and reliable material that can be used as a tool in health education and serve as a source of guidance for adolescents living with type 1 diabetes, promoting adherence and self-management of treatment.